Evaluation du Microbiote du Poisson, cas de la Sardine, Merlu, et la Bonite. - TERMOUL, CHAREF; ONITER, HOUARI (My University, 2020)
Seafood products play a very important role in human nutrition, which is able to provide elements (lipids, calories, vitamins, etc.), and especially proteins essential for human nutrition. Because of its nutritional qualities but also for the wide choice it offers in terms of taste, texture or the form in which it is marketed. Indeed, fresh fish is the most important element in both local and international markets. Fish is cited among the most alterable seafood products thanks to the richness of its chemical composition in nutrients favorable for the proliferation of pathogenic germs, it is a fragile product highly degradable under the action of temperature and atmospheric conditions. external. This present work has to assess the microbiological quality of a sardine species (Sardina pilchardus), which is appreciated by consumers for its high protein profile and on the other hand for its price. In our study, we looked at the microbiological evolution of sardines bought at the port and market of Mostaganem. Microbiological analyzes showed a slight difference in the microbial load in the species purchased at the port as well as at the market but which remains within the range of standards (38.101 CFU / g at the market as well as at the port 25.101 CFU / g) . The results obtained showed good stability of the original organoleptic parameters of sardines and microbiological quality meeting standards.
Keywords: Sardina pilchardus; sanitary quality; freshness; organoleptic quality